13C Tracking after 13CO2 Supply Revealed Diurnal Patterns of Wood Formation in Aspen. Issue 2 (30th April 2015) - Mahboubi, Amir; Linden, Pernilla; Hedenström, Mattias; Moritz, Thomas; Niittylä, Totte
Abstract : 13 C incorporation provides insight into the temporal dynamics of wood formation in hybrid aspen. Abstract: Wood of trees is formed from carbon assimilated in the photosynthetic tissues. Determining the temporal dynamics of carbon assimilation, subsequent transport into developing wood, and incorporation to cell walls would further our understanding of wood formation in particular and tree growth in general. To investigate these questions, we designed a 13 CO2 labeling system to study carbon transport and incorporation to developing wood of hybrid aspen ( Populus tremula × tremuloides ). Tracking of 13 C incorporation to wood over a time course using nuclear magnetic resonance spectroscopy revealed diurnal patterns in wood cell wall biosynthesis. The dark period had a differential effect on 13 C incorporation to lignin and cell wall carbohydrates. No 13 C was incorporated into aromatic amino acids of cell wall proteins in the dark, suggesting that cell wall protein biosynthesis ceased during the night. The results show previously unrecognized temporal patterns in wood cell wall biosynthesis, suggest diurnal cycle as a possible cue in the regulation of carbon incorporation to wood, and establish a unique 13 C labeling method for the analysis of wood formation and secondary growth in trees.